2018
DOI: 10.18502/kls.v4i4.2304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Stress on Body Weight, Blood Pressure, and Urine Specific Gravity among Underground Miners in PT X 2015

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…They were also informed of the aim and method of the study. If the body temperature reaches more than 38.5 degrees Celsius, the person feels dizzy, nauseous, or weak, or the heart rate reaches the maximum threshold according to Eq (1), the experiments will be stopped [3,37].…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were also informed of the aim and method of the study. If the body temperature reaches more than 38.5 degrees Celsius, the person feels dizzy, nauseous, or weak, or the heart rate reaches the maximum threshold according to Eq (1), the experiments will be stopped [3,37].…”
Section: Participantsmentioning
confidence: 99%
“…Exposure to warm air conditions in the workplace can directly or indirectly affect employees’ physiological responses, such as body temperature, metabolism rate, heart rate (HR), and blood pressure [ 1 3 ]. It can cause heat-related illnesses, including heat exhaustion, muscle cramps, heatstroke, heat rashes, and neuropsychiatric disorders [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat is a work environment factor that is very closely related to the health of workers [6] and must be seriously addressed since it strains the body, which may lead to discomfort, heart disease and even death [7,8]. Workers in various industries, such as mining, construction, manufacturing, and agriculture, are exposed to health hazards [9].…”
Section: Introductionmentioning
confidence: 99%
“…The study also unveils the relationship between indoor temperature and heat-related health problems in the elderly. It is shown that the indoor environment could pose higher health risks than the outdoor environment [9]. Workers engaged in jobs involving operations under elevated air temperatures and humidity, or demanding physical activities, are at significant risk of experiencing heat stress [10].…”
Section: Introductionmentioning
confidence: 99%